Serum-25-hydroxycholecalciferol levels in children and adolescents - Gültekin, Asım; Özalp, İmran and Hasanoğlu, Alev and Ünal, Ahmet (The Turkish Journal of Pediatrics, 1987)
This study was carried out to determine the relation between the nutritional status and serum-25-hydroxycholecalciferol levels in school age children. In Group I, whose diet mainly consisted of vegetable source foods, vitamin D deficiency was recorded as 15.9 percent while in Group I, whose nutrition was more balanced, this figure was 5 percent. This finding led us to believe that vitamin D deficiency in our country is an important problem not only in infancy but also in school-age children, especially in adolescent girls.